The Effect of Rotational Tool Speed on Dissimilar Joint Aluminum-Copper Plate Friction Stir Welded Joint - Nugroho, Aris Widyo; Rahman, Khukuh Aulia; Rahman, Muhammad Budi Nur (Universitas Muhammadiyah Yogyakarta, 2023)
The study investigates the impact of rotational tool speed on the mechanical properties and microstructure of aluminum-cooper friction stir-welded joints. It found that higher rotational speed leads to increased grain size, possibly due to increased heat production. Higher hardness values in the stir zone result from uniform dispersion of smaller copper particles. The study found that 540 rpm yields the maximum hardness value in the stir zone, measuring 67 VHN. However, higher speed results in defects like voids, cracks, and intermetallic compounds (IMCs), which are linked to the formation of IMCs at elevated temperatures. The optimal welding conditions at 550 rpm balance grain refinement, hardness enhancement, and defect mitigation, contributing to the understanding of welding process parameters.